Citrus Canker: An Established Infection in the Florida Citrus Industry - Jamie D. Yates; Timothy M. Spann; Michael E. Rogers; Megan M. Dewdney (EDIS)
CH199, a full-color tri-fold brochure by J.D. Yates, T.M. Spann, M.E. Rogers, and M.M. Dewdney, provides key information on the history, spread, symptoms, and management of this serious disease affecting the citrus industry. Includes references and contact list. Published by the UF Department of Horticultural Sciences, July 2008.